Stupendous, miserable city : Pasolini's Rome - Rhodes, John David, 1969- (University of Minnesota Press, 2007)
John David Rhodes places the city of Rome at the center of this original and in-depth examination of the work of Italian director Pier Paolo Pasolini-but it's not the classical Rome you imagine. Stupendous, Miserable City situates Pasolini within the history of twentieth-century Roman urban development. The book focuses first on the Fascist period, when populations were moved out of the urban center and into public housing on the periphery of the city, called the borgate, and then turns to the progressive social housing experiments of the 1950s. These environments were t.